Pinewood VOC emissions protect from oxazolone-induced inflammation and dysbiosis in a mouse model of atopic dermatitis - Evelyn Schneider; Yacine Amar; Katja Butter; Katja Steiger; Stephanie Musiol; Manuel Garcia-Käufer; Inga Marie Hölge; Benjamin Schnautz; Silvia Gschwendtner; Andrea Ghirardo; Richard Gminski; Bernadette Eberlein; et al. (Environment International, 2024)
Pinewood, increasingly used in construction and interior fittings, emits high amounts of volatile organic compounds (VOCs), which tend to accumulate in indoor air. Whether indoor VOCs affect the development of atopic dermatitis (AD) is a matter of debate. We aimed to evaluate the effects of pinewood VOCs on the development of AD-like inflammatory phenotype and linked microbiome alterations, both hallmarks of AD. An oxazolone-induced mouse model of AD was exposed to three different VOC concentrations emitted by pinewood plates throughout the experiment. The disease course and associated immunological and microbiological changes were evaluated. To validate and translate our results to humans, human keratinocytes were exposed to a synthetic pinewood VOCs mixture in an AD environment. Pinewood emitted mainly terpenes, which at a total concentration of 5 mg/m3 significantly improved oxazolone-induced key AD parameters, such as serum total IgE, transepidermal water loss, barrier gene alteration, inflammation, and dysbiosis. Notably, exposure to pinewood VOCs restored the loss of microbial richness and inhibit Staphylococci expansion characteristic of the oxazolone-induced mouse AD model. Most beneficial effects of pinewood VOCs were dose-dependent. In fact, lower (<3 mg/m3) or higher (>10 mg/m3) pinewood VOC levels maintained only limited beneficial effects, such as preserving the microbiome richness or impeding Staphylococci expansion, respectively. In the human in-vitro model, exposure of keratinocytes grown in an AD environment to a pinewood VOCs mixture reduced the release of inflammatory markers. In conclusion, our results indicate that airborne phytochemicals emitted from pinewood have beneficial effects on an AD-like phenotype and associated dysbiosis. These investigations highlight the effects of terpenes as environmental compounds in the prevention and/or control of atopic skin disease.